KALAPANI, LIPULEKH, LIMPIYADHURA DISPUTE AND CHALLENGES IN INDIA-NEPAL RELATIONS - Kumar, Pardeep; Kumar, Navin (ShodhKosh: Journal of Visual and Performing Arts, 2023)
Geographical location, socio-cultural environment, economic interdependence, have had a great influence in determining the relations between India and Nepal. In fact, there are very few countries in the world that are so closely intertwined with each other as India and Nepal. A clear depiction of person to person relations is seen in India-Nepal relations. The open border of both countries has further enriched this closeness. India is an important and large ally of Nepal. India has the most trade partners with Nepal and also has the highest foreign investment etc. However, sometimes border disputes between the two become serious issues. The recent border dispute is related to the Kalapani region, which has affected relations between the two countries because both present historical evidence in their favor. The current border dispute has seriously impacted both the countries, which were considered to have an open border and served as a model for the world. China is increasing its role in the India-Nepal border dispute. Therefore, in this research paper, we will describe how India and Nepal can resolve this border dispute, considering their historical relations. India and Nepal can resolve their border dispute in a formal and friendly manner. What changes will the resolution of this border dispute bring to the relations between the two countries and what is the importance of this border dispute in India’s foreign policy?